Luontomatkailun vaikutukset Käsivarren erämaa-alueen luontoon - Lahti, Tuomas (Helsingfors universitet, 2014)
The purpose of this master's thesis was to study environmental impacts of nature-based tourism on vegetation, insect communities, birds and soil nitrogen levels in Käsivarsi wilderness area in the Finnish Lapland. Tourism is the largest industry in the world and nature-based tourism is the fastest growing segment of it. Nature-based tourism takes place in areas that holds great nature values. These areas are often protected to preserve significant nature values from negative impacts of human activities. This controversy creates disharmony between nature tourism and nature conservation. Most popular nature tourism destinations in Finland are state owned national parks and wilderness areas. Wilderness areas are not within strict nature conservation. They are areas defined by law for preserving the typical character of the remaining wilderness areas, preserving native Saami culture and for preserving and developing recreational use of these areas. Studies have shown that nature-based tourism has caused changes by erosion and human disturbance to vegetation, mammals and birds. The key study question was to examine if there are changes in the soil nitrogen levels around huts used by hikers. I was also a point of interest to discover what kind of bird, insect and plant communities occur around these huts. Main interest was to see if there are changes in these communities on a gradient from high human impact areas around the huts to more pristine mountainous areas. The study was performed around five huts with three study lines, which had study points 15, 30, 60, 120, 240, 480 and 960 meters away from the hut. Birds were observed from the same lines but with 200 meter point counting intervals. It was also studied whether the abundance of graminoids was affected by the soil nitrogen levels and if soil nitrogen levels or the abundance of graminoids influenced changes in insect or bird communities. Results show that nature-based tourism has an impact on soil ammonium and nitrate levels. This impact was visible in ...